Immune dysfunction in patients with end stage kidney disease; Immunosenescence - Review - Bumbea Viorica Ileana; Bumbea Horia; Vladareanu Ana Maria (Sciendo, 2024)
The body's defense against environmental factors is realized by physical barriers and cells of both the innate and adaptive immune systems. Patients with end stage kidney disease (ESKD), especially those treated by hemodialysis, have changes in both the function and the number or percent of different leukocyte subsets. Changes were described at the level of monocytes and lymphocyte subsets, which are associated with immunodeficiencies and pro-inflammatory status correlated with degenerative changes and increased cardiovascular risk. These abnormalities have been compared over the past years with alterations appearing as a result ageing. Also, similitudes regarding immunosenescence observed in ESKD patients, in combination with chronic inflammation, are described as the so-called "inflammaging syndrome".